2021
DOI: 10.1186/s40001-021-00606-7
|View full text |Cite
|
Sign up to set email alerts
|

A fresh look at the role of spiramycin in preventing a neglected disease: meta-analyses of observational studies

Abstract: Purpose We aimed to investigate the effect of antepartum treatment with spiramycin with or without subsequent pyrimethamine–sulfonamide–folinic acid, compared to no treatment, on the rate of mother-to-child transmission (MTCT) of Toxoplasma gondii (T. gondii) and incidence/severity of sequelae in the offspring. Methods Embase and PubMed were searched for literature on spiramycin in pregnant women suspected/diagnosed with T. gondii infection. Meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
0
8
0
1
Order By: Relevance
“…Herein, we present an introduction to, and an overview and review of work [ 1 ••, 2 , 3 ••, 4 ••, 5 ••, 6 ••, 7 ••, 8 ••, 9 ••, 10 ••, 11 ••, 12 , 13 , 14 ••, 15 ••, 16 ••, 17 ••, 18 •, 19 •, 20 •, 21 •, 22 •, 23 , 24 ••, 25 , 26 , 27 •, 28 •, 29 , 30 , 31 •, 32 •, 33 ••, 34 •, 35 •, 36 , 37 •, 38 •, 39 ••, 40 •, 41 •, 42 ••, 43 ••, 44 ••, 45 , 46 •, 47 ••, 48 ••, 49 , 50 •, 51 •, 52 •, 53 ••, 54 , 55 ••, 56 ••, 57 •, 58 ••, 59 •, 60 ••, 61 , 62 ••, 63 •, 64 ••, 65 , 66 ••, 67 ••, 68 ••, 69 , 70 , 71 ••, 72 ••, 73 •...…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we present an introduction to, and an overview and review of work [ 1 ••, 2 , 3 ••, 4 ••, 5 ••, 6 ••, 7 ••, 8 ••, 9 ••, 10 ••, 11 ••, 12 , 13 , 14 ••, 15 ••, 16 ••, 17 ••, 18 •, 19 •, 20 •, 21 •, 22 •, 23 , 24 ••, 25 , 26 , 27 •, 28 •, 29 , 30 , 31 •, 32 •, 33 ••, 34 •, 35 •, 36 , 37 •, 38 •, 39 ••, 40 •, 41 •, 42 ••, 43 ••, 44 ••, 45 , 46 •, 47 ••, 48 ••, 49 , 50 •, 51 •, 52 •, 53 ••, 54 , 55 ••, 56 ••, 57 •, 58 ••, 59 •, 60 ••, 61 , 62 ••, 63 •, 64 ••, 65 , 66 ••, 67 ••, 68 ••, 69 , 70 , 71 ••, 72 ••, 73 •...…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we confirmed the possibility of applying an old weapon, spiramycin, to various inflammatory diseases, the new enemy. Spiramycin has been shown to exhibit anti-bacterial, anti-viral, and anti-parasitic activities [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. However, no study has reported the anti-inflammatory potential of spiramycin in LPS-induced macrophage RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Spiramycin is a 16-membered ring macrolide antibiotic that was first discovered 70 years ago in a culture medium of Streptomyces ambofaciens in 1952 ( Figure 1 ). The antibiotic action of spiramycin, which inhibits protein synthesis in bacterial cells during translocation, has high antimicrobial activity against Gram-positive bacteria and mycoplasma species, and is widely used to treat toxoplasmosis and other soft-tissue infections in cattle, pigs, poultry, and sheep [ 6 , 7 , 8 ]. Spiramycin is prescribed in some countries for various odor-causing infections including periodontitis [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Part IV considers briefly the foundation to which these studies contribute, providing a rationale and framework for extending the studies. This includes additional basic science and translational work and needed improvements in clinical care [ 1 ••, 2 , 3 ••, 4 ••, 5 ••, 6 ••, 7 ••, 8 ••, 9 ••, 10 ••, 11 ••, 12 , 13 , 14 ••, 15 ••, 16 ••, 17 ••, 18 •, 19 •, 20 •, 21 •, 22 •, 23 , 24 ••, 25 , 26 , 27 •, 28 •, 29 – 30 , 31 •, 32 •, 33 ••, 34 •, 35 •, 36 , 37 •, 38 •, 39 ••, 40 •, 41 •, 42 ••, 43 ••, 44 ••, 45 , 46 •, 47 ••, 48 ••, 49 , 50 •, 51 •, 52 , 53 ••, 54 , 55 ••, 56 ••, 57 •, 58 ••, 64.•• ••, 68 ••, 88 ••, 89 ••, 90 , 91 , 92 ••, 93 , 94 , 118 ••, 124 , 125 …”
Section: Introductionmentioning
confidence: 99%